Heavy metals released from sewage sludge of Basrah city, Iraq using chemical method - Ibrahim, F.H. (Mesopotamian Journal of Marine Sciences, 2022)
Samples of anaerobically digested sludge were obtained from the anaerobic unit of a waste water plant in Abo Al-Kaseeb (Basrah, Iraq) during 2012. The removal of heavy metals (Pb, Cu and Zn) were studied using sulphuric acid as a chelating agent by using A.A. Spectrophotometry. Metal removal was found to be depending on pH, solid concentration, specific types of metals and period of acidification. The rate of removal efficiency and solubilisation increased with time, low pH and low solid concentration. Limitation in solubilisation were existed, regardless of the period of acidification dependent on pH, and solid concentrations of the metal. The pattern of metals solubilisation with respect to time was similar. It increased to reach a maximum solubilisation in a relatively short period of time, and then remained the same for the duration of the 24 hrs. acidification period. This is a leading work which may open a future studies in the treatment of sewage sludge in Basrah city